Sistema de toma de decisiones nivel administrativo para la distribuidora de insumos agrícolas “AGROLIVE” - Bernal Villamar Héctor Omar, Héctor Omar (2020)
Development of an administrative level decision-making system for the agricultural input distributor “Agrolive”. The software was developed applying the HEFESTO methodology, it allows the construction of the Data Warehouse in a simple, orderly and intuitive way, to be able to adapt to any software development life cycle.  Analysis of requirements TP OLTP analysis  Logical model of the data warehouse  ETL processes A Data warehouse allows integrating data from multiple source systems, allows a central vision throughout the company for its ability to analyze data from multiple sources using ETL processes (extraction, transformation, reading). This process optimizes decision making by strengthening operations, in order to generate competitive and successful operations.